2022
DOI: 10.5603/cj.a2022.0045
|View full text |Cite
|
Sign up to set email alerts
|

The diagnostic and prognostic value of copeptin in patients with acute ischemic stroke and transient ischemic attack: A systematic review and meta-analysis

Abstract: Background Stroke is the second main cause of mortality and the third leading cause of mortality and permanent disability combined. Many potential biomarkers have been described to contribute to the diagnosis, prognosis of outcomes, and risk stratification after stroke. Copeptin is an inactive peptide that is produced in an equimolar ratio to arginine vasopressin in response to the activation of the endogenous stress system. Methods The present study is a systematic rev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…It has been shown that cerebral ischemia may increase AVP levels in the plasma of patients with stroke ( 212 , 213 ) and that V1R, but not V2R, is involved in the pathophysiology of secondary brain damage after focal cerebral ischemia ( 214 ). A meta-analysis revealed mean copeptin levels in different groups: stroke and non-stroke groups (19.8 ± 17.4 vs. 9.7 ± 6.6 pmol/L, respectively), good vs. poor outcome groups (12.0 ± 3.6 vs. 29.4 ± 14.5 pmol/L, respectively), and survive vs. non-survive stroke patients (13.4 ± 3.2 vs. 33.0 ± 12.3, respectively) ( 215 ), suggesting copeptin may guide the management of stroke patients. Interestingly, no significant difference was observed between the stroke group and stroke mimics (diseases with symptoms frequently seen in patients with stroke but caused by non-cerebrovascular pathogeneses) groups ( 216 ), indicating that copeptin could not discriminate between stroke and stroke mimics.…”
Section: Copeptin In Strokementioning
confidence: 99%
“…It has been shown that cerebral ischemia may increase AVP levels in the plasma of patients with stroke ( 212 , 213 ) and that V1R, but not V2R, is involved in the pathophysiology of secondary brain damage after focal cerebral ischemia ( 214 ). A meta-analysis revealed mean copeptin levels in different groups: stroke and non-stroke groups (19.8 ± 17.4 vs. 9.7 ± 6.6 pmol/L, respectively), good vs. poor outcome groups (12.0 ± 3.6 vs. 29.4 ± 14.5 pmol/L, respectively), and survive vs. non-survive stroke patients (13.4 ± 3.2 vs. 33.0 ± 12.3, respectively) ( 215 ), suggesting copeptin may guide the management of stroke patients. Interestingly, no significant difference was observed between the stroke group and stroke mimics (diseases with symptoms frequently seen in patients with stroke but caused by non-cerebrovascular pathogeneses) groups ( 216 ), indicating that copeptin could not discriminate between stroke and stroke mimics.…”
Section: Copeptin In Strokementioning
confidence: 99%
“…AVP release stimulates V1a and V2 receptors, which then cause platelet aggregation, vasoconstriction, and water retention with low plasma osmolality and hypovolemic or euvolemic hyponatraemia as consequences with resultant infarct volume expansion. This is the first study we are aware of that looked into the relationship between copeptin level, ischaemic stroke severity, and infarct volume in the country [ 22 , 33 , 34 ].…”
Section: Discussionmentioning
confidence: 99%
“…A glycopeptide of 39 amino acids, copeptin is a fragment of the prohormone pre-pro-vasopressin, which is a precursor to vasopressin. Inside the posterior pituitary gland, pre-pro-vasopressin is cleaved into copeptin and vasopressin, which are circulating in equimolar amounts ( Blek et al, 2022 ). The serum copeptin level is a marker of vasopressin secretion due to its high stability, and reflects the degree of activation of hypothalamic–pituitary–adrenal-axis in IS patients ( Jalleh and Torpy, 2021 ).…”
Section: Specific Biomarkers For Disease Burden and Outcomes For Pati...mentioning
confidence: 99%